Best of times, worst of times : contemporary American short stories from the new Gilded Age - Martin, Wendy, 1940-; Tichi, Cecelia, 1942- (New York University Press, 2011)
A collection of short stories depicting and analyzing key issues in America's "New Gilded Age", a phrase that embodies the glitz and glamour of one of the wealthiest countries in the world but also suggests the greed, corruption, and inequalities teeming just below the surface.